Appraisal of Trained Manpower Requirements for Forestry Development in India - Seth, V. K. (Indian Forester, 1973)
In this paper an appraisal has been done of trained manpower requirements in the forestry and forest-industries sectors for the year 1985 based on prognoses of demands for industrial wood and fuelwood. Norms have been adopted for working out requirements of technicians (Rangers) based on F.A.O. studies and experience in the field. The requirements of supervisory staff (Officers) have been worked out by adopting supervision ratios. Based on a projected demand in 1985 of 50 million cubic metres of industrial wood and 300 million cubic metres of fuelwood, the requirement of technicians and officers works out to 30,000 and 7500 respectively in round figures as against the 1970 figures of 6000 and 1900. To fill this large gap nearly 500 officers and 2000 technicians will have to be trained annually with an input of Rs. 20 million. For this purpose more training institutions and centres will be required. There is a pressing need for an evaluation of national manpower requirements in the forestry sector and integrating human resources planning with economic development. It is hoped that this study will help in the identification, formulation and operation of new projects in the field of forestry education, the establishment of priorities and the coordination of the efforts of governments and industries.